2015
DOI: 10.17795/ijcp-3983
|View full text |Cite
|
Sign up to set email alerts
|

Non Invasive XRF Analysis of Human Hair for Health State Determination of Breast Tissue

Abstract: Background:Using hair samples to analyze the trace element concentrations is of interest among many researchers. X-ray fluorescence (XRF) and X-ray diffraction (XRD) are the most common methods in studying the structure and concentration of elements of tissues and also crystalline materials, using low energy X-ray.Objectives:In the present study, the detection ability of Wave Length X-ray Fluorescence (WLXRF) of breast cancer at early stages was evaluated and the results were compared with other routine modali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, hair samples have been used to assess the risk of breast cancer [85]. With XRF and X-ray diffraction techniques, it was shown that not only elemental levels but also hair structure differ between healthy controls and those with breast cancer [86]. More specifically, the data revealed that trace element levels were higher in healthy controls than in breast cancer patients and that wavelength of XRF presented with a 96% sensitivity compared to a 77% sensitivity for mammography, the gold standard for breast cancer screening.…”
Section: Oncologymentioning
confidence: 99%
“…Interestingly, hair samples have been used to assess the risk of breast cancer [85]. With XRF and X-ray diffraction techniques, it was shown that not only elemental levels but also hair structure differ between healthy controls and those with breast cancer [86]. More specifically, the data revealed that trace element levels were higher in healthy controls than in breast cancer patients and that wavelength of XRF presented with a 96% sensitivity compared to a 77% sensitivity for mammography, the gold standard for breast cancer screening.…”
Section: Oncologymentioning
confidence: 99%